Hadis Populer Tentang Ilmu dan Relevansinya dengan Masalah Pendidikan Islam - Irham Irham (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The Popular Hadith Concerning Knowledge and its Relevance to the Problems of Islamic EducationComprehensive studies on hadiths in terms of sanad, matan, and sharah should be done in order to get a good understanding. This article aims to explain comprehensively a popular hadith as regards the command to study. The takhrij method is used to find the qualities of sanad and matan. Furthermore, it gives sharah on the hadiths especially in the term